Study of glycolic acid and salicylic acid peels as a sole therapy in treatment of acne vulgaris - Sharma, Parikshit; Shah, Akhil; singh Dhillon, Alamjit (International Journal of Medical Research and Review, 2016)
Introduction: Acne vulgaris is a very common physiological condition of adolescents, better regarded as a disease due to some inflammatory component. In spite of various modalities of treatment available, it still poses a therapeutic problem to the dermatologists. The advent of new and potent topical therapeutic modalities such as chemical peeling has resulted in significant improvement in the treatment of acne. This study aims to observe the therapeutic response of two chemical peels, 35% glycolic acid and 30% salicylic acid on active acne lesions, when given as monotherapy. Materials & Methods: A total of 200 patients of either sex with acne were randomly selected and enrolled for the study, two groups of 100 patients each were made of 35% GA and 30% SA respectively. No other concurrent therapy was given. Individual lesions of each type were calculated before and after completing 6 treatment sessions and the numbers were observed to know the effect of both the acids on different types of lesions. Results: After 6 sessions, in the glycolic acid group the reduction in average number of comedones was 88.45%, inflammatory papules 88.65%, pustules 89.62% & nodules/cysts 83.33%. Whereas, in the Salicylic acid group, the reduction was 89.00%, 90.36%, was 84.87% & 100% in comedones, papules, pustules & nodules/cysts respectively. Conclusion: In our observation, both 35% glycolic acid and 30% salicylic acid are significantly effective as monotherapy in patients of acne. They not only clear the acne lesions but also show improvement in post acne scar and hyperpigmentation to some extent.